"I Would Say It's Almost Like a Crime Against, You Know, the Soul": Building a Culture of Health in Low-Income Housing Communities Through Addressing Childhood Trauma. Issue 3 (4th May 2019) - Barrera, Irán; Kelley, Sabrina; Aratani, Yumiko
ABSTRACT: The purpose of this article is to examine parental perceptions of child maltreatment to inform services that target families living in low-income housing communities in Fresno, California, through focus group interviews. We identified three main themes across all focus group interviews that describe the child maltreatment among our participants: (a) acknowledging child maltreatment as a problem, and its negative consequences; (b) normalizing or justifying child maltreatment as part of growing up; and (c) seeing child maltreatment as intergenerational. Additionally, parents discussed types of help to address child maltreatment. We then propose a prevention model using a public health framework along with other policy recommendations that highlight the importance of culturally and linguistically appropriate services for diverse families living in low-income housing communities.